Exploration of Copper and Lead Resistant Bacteria from Sediments of Kali Baru Estuary - Purnomo, Eko; Kusumaningrum, Hermin Pancasakti; Budiharjo, Anto; Lunggani, Arina Tri; Az-Zahra, Salwa Zubaidah; Wardaja, Bodhicitta; Maimunah, Siti; Dinalhaq, Putri Cahya (Universitas Brawijaya, 2026)
Heavy metal contamination, particularly by copper (Cu) and lead (Pb), in aquatic ecosystems poses a significant threat to ecological balance, aquatic organisms, microbial diversity and human health. The Kali Baru Estuary in Semarang, Indonesia, has been reported as a heavily polluted area with Cu and Pb concentrations far exceeding environmental safety thresholds, highlighting the urgent need for sustainable remediation strategies. This study aimed to isolate and characterise bacterial strains resistant to Cu and Pb from sediment samples collected from the Kali Baru Estuary in Semarang as potential bioremediation agents. Bacterial isolation was performed using a serial dilution technique up to 10?², in triplicate, spread onto Marine Agar medium, and incubated at 37°C for 24 h. The obtained isolates were purified and characterised based on their macroscopic and microscopic morphological features. Resistance profiling of the isolates was assessed by exposing them to Cu and Pb at concentrations of 100, 200, and 300 mg/L. A total of 32 bacterial isolates were successfully obtained. Among these, two isolates demonstrated resistance to Cu, and 14 isolates exhibited resistance to Pb at the highest concentration tested (300 mg/L). These metal-resistant bacterial isolates exhibit substantial promise for bioremediation applications aimed at remediating Cu and Pb-contaminated aquatic environments.